Ulul Albab generation: roles of Ulul Albab teachers in Malaysian selected school - Subirim @ Subirin, Nor Adzimah; Alwi, Nor Hayati; Mohd Fakhruddin, Fathiyah; Abdul Manaf, Umi Kalthom; Salim, Siti Suria (Human Resource Management Academic Research Society, 2017)
Since Ulul Albab program has been introduced in several government schools few years ago, it has become a craze among the society and the demand is increasing because of its uniqueness features and the goals it promotes. After analysing the concept of Ulul Albab and its characteristics, however, a huge task on the shoulders of the teachers is needed to carry out the programme. Ulul Albab as defined by many scholars is a term given to gifted individuals who possess wisdom, intelligence and knowledge based on belief and devotion to Allah (SWT) and this is not an ordinary term. The Ulul Albab program is established by taking Ulul Albab in the Al-Quran as the basis for the curriculum, therefore, it requires factors that may contribute to the achievement of an Ulul Albab generation to be analysed and examined continuously. Teachers as the key implementer of the program are seen to have a big role and responsibility towards achieving the goals and objectives. Various studies have shown that there exists a significant relationship between teachers’ effectiveness and students’ achievement. Specifically, this special program requires special trained teachers to run the program effectively. It is not too much to say then that teachers act as the mediators of the Ulul Albab generation. By saying this, teachers’ professional development programme for Ulul Albab pre-service and in-service teachers have become vital in order to enhance the quality of the Ulul Albab teachers in order to effectively run the programme. These quality teachers will then become an effective role-model for the Ulul Albab students.